Mixed gonadal dysgenesis in Yaoundé: A preliminary experience about three cases - F F Mouafo Tambo; S Dahoun; C Kamadjou; A S Nwaha Makon; G Fossi; O G Andze; M A Sosso; P Y Mure (Wolters Kluwer Medknow Publications, 2016)
Mixed gonadal dysgenesis is characterised by unilateral chromosomal abnormality, which is probably the result of anaphase lag during mitosis. The 45, XO/46, XY karyotype is the most common form of mosaicism involving the Y chromosome. It is a rare clinical entity with a worldwide incidence of 1.5/10,000 live births. Its epidemiology in Sub-Saharan Africa is not known. This study reports experience in the management of 3 cases at the Yaounde Gynecologic-Obstetric and Paediatric Hospital. From November 2009 to November 2014, 3 cases were successfully managed at our institution. Results: All patients presented with asymmetrical gonadal differentiation. On one side of the body, a poorly-developed testicular gonad and on the other side a gonadal streak. A persistent Mόllerian remnant was equally found in the 3 cases. Management of mixed gonadal dysgenesis should be done in tertiary health care centres. A multidisciplinary team approach is recommended.